PELAKSANAAN PEMERINTAHAN DESA DI DESA KARANGUDI, KECAMATAN NGRAMPAL, KABUPATEN SRAGEN SESUAI DENGAN UNDANG-UNDANG NO. 6 TAHUN 2014 - SUWARNO, SUWARNO (Dinamika Hukum, 2017)
The purposes of this research are to study and analyze the implementationof the village unitâ€™ task according to Act Number 6 of 2014 and to study andanalyze the roles of Village Institution for Community Empowerment andDevelopment (Lembaga Pemberdayaan Pembangunan Masyarakat Desa(LP2MD)) in embracing peopleâ€™s aspiration in the field of village development inorder to create democracy in Karangudi Village.The background of the implementation of rural development forempowerment in accordance to Act Number 6 Year 2014. This is as aconsequence of the central government's desire the establishment of ruraldevelopment in harmony with progress nationwide in the countryside.This research used a kind of juridical sociological research. The locationselected is in Karangudi Village, Ngrampal Sub-district, Sragen Regency. Thecharacteristics of this research is descriptive that according to Soerjono Soekamtois â€œa research that provides an initial data as carefully as possible about human,condition or other symptomsâ€. Object of the research is the nature of the villagegovernance in the regional autonomy era. The data sources were obtained throughserveral information or facts from the Village Unit, the Village Secretary, theVillage Apparatuses, and the Villagers of Karangudi Village, Ngrampal Subdistrict,Sragen Regency.The results of the research is that one of village deliberations held inKarangudi Village is the Deliberation of Village Development Planning(Musyawarah Perencanaan Pembangunan Desa (Musrenbangdes)). theDeliberation of Village Development Planning (Musrenbangdes) is a kind ofvillage discussion attended by the elements of Village Government, VillageConsultative Body (Badan Permusyawaratan Desa (BPD)), village societalassembly, one of them is the Village Institution for Community Empowermentand Development (LP2MD) and held once a year in the office of KarangudiVillage. In the Deliberation of Village Development Planning (Musrenbangdes),the Village Institution for Community Empowerment and Development (LP2MD)is the village societal institution that involved in the deliberation.Keywords: the role of village and rural development.